2008
DOI: 10.1242/jeb.015081
|View full text |Cite
|
Sign up to set email alerts
|

The responses of Atlantic cod (Gadus morhua L.) to ultrasound-emitting predators: stress, behavioural changes or debilitation?

Abstract: SUMMARYA previous study has reported that Atlantic cod can be conditioned to detect ultrasonic sound pulses of high intensity. This capability has been proposed as a mean for detection and avoidance of echolocating toothed whales that emit intense ultrasonic clicks. In this study, we use acoustic playbacks to test the hypotheses that unconditioned cod can detect and respond to intense ultrasound from toothed whales and from echosounders. Intense ultrasound exposure of 210 dB re. 1 μPa (pp) did not cause a shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…Fish movements were video recorded (30 frames/second) from the side for 5 min before and after stimulus addition (180 l of odor or tank water as control) by an experimenter not visible to the fish. Fish movements were video recorded for 5 min before and after stimulus addition (180 l of 1 mM 4-hydroxyphenylacetic acid or water) and tracked using LoliTrack version 3 automated motion tracker (12). Distance to the odor source and velocity were determined using Open Office (Apache).…”
Section: Methodsmentioning
confidence: 99%
“…Fish movements were video recorded (30 frames/second) from the side for 5 min before and after stimulus addition (180 l of odor or tank water as control) by an experimenter not visible to the fish. Fish movements were video recorded for 5 min before and after stimulus addition (180 l of 1 mM 4-hydroxyphenylacetic acid or water) and tracked using LoliTrack version 3 automated motion tracker (12). Distance to the odor source and velocity were determined using Open Office (Apache).…”
Section: Methodsmentioning
confidence: 99%
“…The observation by Astrup and Mohl (1993) that cod (Gadus morhua) detect ultrasound at 38 kHz could not be confirmed by studies. Schack et al (2008) showed that unconditioned cods do not respond to ultrasound and thus will not react to toothed whale vocalizations. Further support for the predator avoidance hypothesis comes from the observation that many fish species avoid predators using a C-like startle behavior (C-start; Canfield and Eaton, 1990;Canfield and Rose, 1996).…”
Section: Why Hearing Enhancement In Fishes?mentioning
confidence: 99%
“…Cod (Gadus morhua) can be conditioned to detect ultrasound stimuli (Astrup and Møhl, 1993) and to discriminate between long and short pulse intervals (Astrup and Møhl, 1998). However, a recent study of unconditioned cod showed that they did not respond behaviourally to intense ultrasonic stimuli (Schack et al, 2008). Whether behaviours of fish to ultrasound evolved in response to odontocete predation has been discussed (Astrup, 1999), but still remains unknown.…”
Section: Introductionmentioning
confidence: 99%